2009
DOI: 10.1007/s11104-009-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution pattern of soil seed bank in canopy gaps of various sizes in temperate secondary forests, Northeast China

Abstract: To promote the natural regeneration of secondary forests under gap disturbance is one of important approaches for realizing their restoration and sustainable management. However, soil seed bank, one of regeneration strategies, is poorly understood in gaps of secondary forests. Objectives of the study were to evaluate the effects of sizes of experimentally created gaps on seed distribution in soil, and of seed banks on vegetation recovery at early formation stage of gaps in temperate secondary forests, Northeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
(48 reference statements)
1
29
1
Order By: Relevance
“…The results showed that more than 90% of the seeds in seed rain were wind-dispersed, and their seed rain density and the contribution of seed rain to soil seed bank in medium gaps reached the highest (p = 0.03). The results suggest that establishing medium-sized gaps (i.e., gap size with 150-250 m 2 ) in the secondary forests is more favorable for improving the natural regeneration potential (arrival of seeds and forming soil seed bank) of gap-dependent and wind-dispersed species (e.g., Acer mono) in gaps.be an effective forest restoration strategy due to its low cost and high productivity [4,5]. Successful natural regeneration from seeds is largely dependent on the arrival of seeds, which represents the start of a natural regeneration that links the end of the reproductive cycle of adult plants and subsequent population renewal and recruitment [7].As one of the most important disturbances in secondary forests, canopy gaps created by the fall of single or multiple trees play a critical role in stand dynamics, forest cycle [8], and biodiversity of temperate secondary forests [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that more than 90% of the seeds in seed rain were wind-dispersed, and their seed rain density and the contribution of seed rain to soil seed bank in medium gaps reached the highest (p = 0.03). The results suggest that establishing medium-sized gaps (i.e., gap size with 150-250 m 2 ) in the secondary forests is more favorable for improving the natural regeneration potential (arrival of seeds and forming soil seed bank) of gap-dependent and wind-dispersed species (e.g., Acer mono) in gaps.be an effective forest restoration strategy due to its low cost and high productivity [4,5]. Successful natural regeneration from seeds is largely dependent on the arrival of seeds, which represents the start of a natural regeneration that links the end of the reproductive cycle of adult plants and subsequent population renewal and recruitment [7].As one of the most important disturbances in secondary forests, canopy gaps created by the fall of single or multiple trees play a critical role in stand dynamics, forest cycle [8], and biodiversity of temperate secondary forests [9,10].…”
mentioning
confidence: 99%
“…Successful natural regeneration from seeds is largely dependent on the arrival of seeds, which represents the start of a natural regeneration that links the end of the reproductive cycle of adult plants and subsequent population renewal and recruitment [7].As one of the most important disturbances in secondary forests, canopy gaps created by the fall of single or multiple trees play a critical role in stand dynamics, forest cycle [8], and biodiversity of temperate secondary forests [9,10]. Promoting the natural regeneration of secondary forests under gap disturbances is crucial to the restoration and sustainable management of secondary forests [5,11]. After gap formation in broadleaved secondary forests, there are two sources of natural regeneration: seed regeneration and sprout regeneration.…”
mentioning
confidence: 99%
“…Although it is difficult to compare the size of the seed bank reported by various authors due to methodological differences (Brown 1992), the size of the seed bank we found seems to be higher than that reported in many other temperate forests where size of 6, Tilio-Buxetum hyrcana seed bank was estimated using the seedling emergence method (Table 4). We tried to collect soil seed bank samples with enough area to adequately represent the seed bank floristically, so we increased the seed bank sample size in comparison to other seed bank studies in temperature forests (Ashton et al 1998;Jalili et al 2003;Decocq et al 2004;Amrein et al 2005;Schmidt et al 2009;Yan et al 2010). However, it may have been better to have had a much smaller sample size with less surface area and more replications, instead of two samples of 20 · 20 cm 2 from each plot; that is, more and smaller samples per plot may have increased interpretation of the seed bank characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary experiment indicated that the data from soil seed banks collected from two transects running along the longitudinal and latitudinal axes in each elliptical gap were sufficient to represent the characteristics of a spatial distribution of seed banks [11]. Therefore, in this study we opted to investigate only two transects in practical operation: one longitudinal transect ran along the south-north direction of the canopy gap (in the direction from lower to upper slope) and the other latitudinal transect ran along the east-west direction of the gap (parallel to slope surface) [11]. Sampling points were set 3 m apart along each transect from the gap center to the canopies adjacent to the gaps on all four sides.…”
Section: Methodsmentioning
confidence: 98%
“…The existing secondary forests are also experiencing gap disturbances [10][11]. Forest regeneration is most likely influenced by gap formation [12].…”
Section: Introductionmentioning
confidence: 99%